Fabrication of a triptolide-loaded and poly-γ-glutamic acid-based amphiphilic nanoparticle for the treatment of rheumatoid arthritis - Zhang L (Dove Medical Press, 2018)
Li Zhang,1–3 Junli Chang,1–3 Yongjian Zhao,1–3 Hao Xu,1–3 Tengteng Wang,1–3 Qiang Li,1–3 Lianping Xing,4 Jing Huang,5 Yongjun Wang,1–3,6 Qianqian Liang1–3 1Department of Orthopaedics, Longhua Hospital, 2Institute of Spine, 3Key Laboratory of Theory and Therapy of Muscles and Bones, Ministry of Education, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 4Department of Pathology and Laboratory Medicine, University of Rochester Medical Center, Rochester, NY, USA; 5School of Life Science, East China Normal University, 6School of Rehabilitation Science, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China Abstract: Triptolide (TP) exhibits immunosuppressive, cartilage-protective and anti-inflammatory effects in rheumatoid arthritis. However, the toxicity of TP limits its widespread use. To decrease the toxic effects, we developed a novel nano-drug carrier system containing TP using poly-γ-glutamic acid-grafted di-tert-butyl L-aspartate hydrochloride (PAT). PAT had an average diameter of 79±18 nm, a narrow polydispersity index (0.18), a strong zeta potential (-32 mV) and a high drug encapsulation efficiency (EE1=48.6%) and loading capacity (EE2=19.2%), and exhibited controlled release (t1/2=29 h). The MTT assay and flow cytometry results indicated that PAT could decrease toxicity and apoptosis induced by free TP on RAW264.7 cells. PAT decreased lipopolysaccharides/interferon γ-induced cytokines expression of macrophage (P<0.05). In vivo, PAT accumulated at inflammatory joints, improved the survival rate and had fewer side effects on tumor necrosis factor α transgenic mice, compared to TP. The blood biochemical indexes revealed that PAT did not cause much damage to the kidney (urea nitrogen and creatinine) and liver (alanine aminotransferase and aspartate aminotransferase). In addition, PAT reduced inflammatory synovial tissue area (P<0.05), cartilage loss (P<0.05), tartrate-resistant acid phosphatase-positive osteoclast area (P<0.05) and bone erosion (P<0.05) in both knee and ankle joints, and showed similar beneficial effect as free TP. In summary, our newly formed nanoparticle, PAT, can reduce the toxicity and guarantee the efficacy of TP, which represents an effective drug candidate for RA with low adverse side effect. Keywords: triptolide, rheumatoid arthritis, γ-PGA, tumor necrosis factor α transgenic mice, drug carrier system